Simulation of the hydrodynamic conditions of the eye to better reproduce the drug release from hydrogel contact lenses: experiments and modeling - Pimenta, A. F. R. (2016)
Currently, most in vitro drug release studies for ophthalmic applications are carried out in static sink conditions. Although this procedure is simple and useful to make comparative studies, it does not describe adequately the drug release kinetics in the eye, considering the small tear volume and flow rates found in vivo. In this work, a microfluidic cell was designed and used to mimic the continuous, volumetric flow rate of tear fluid and its low volume. The suitable operation of the cell, in terms of uniformity and symmetry of flux, was proved using a numerical model based in the Navier-Stokes and continuity equations. The release profile of a model system (a hydroxyethyl methacrylate-based hydrogel (HEMA/PVP) for soft contact lenses (SCLs) loaded with diclofenac) obtained with the microfluidic cell was compared with that obtained in static conditions, showing that the kinetics of release in dynamic conditions is slower. The application of the numerical model demonstrated that the designed cell can be used to simulate the drug release in the whole range of the human eye tear film volume and allowed to estimate the drug concentration in the volume of liquid in direct contact with the hydrogel. The knowledge of this concentration, which is significantly different from that measured in the experimental tests during the first hours of release, is critical to predict the toxicity of the drug release system and its in vivo efficacy. In conclusion, the use of the microfluidic cell in conjunction with the numerical model shall be a valuable tool to design and optimize new therapeutic drug-loaded SCLs.